2019
DOI: 10.3390/ma12010192
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydration and Carbonation Progress on the Porosity and Permeability of Cement Pastes

Abstract: This paper presents the results of comprehensive cement paste porosity and gas permeability tests. The tests conducted concerned ordinary Portland cement (OPC) cement pastes with varying water-cement ratios ranging from 0.3 to 0.6. The tests were conducted after the curing of cement paste for 90 days and two years under laboratory conditions. Open porosity was determined using three methods: helium pycnometry, mercury intrusion porosimetry, and water saturation. Permeability was determined using a modified RIL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 47 publications
4
15
0
Order By: Relevance
“…The results indicated that total porosity values for fully carbonated cement pastes were similar for the different water-to-cement ratios studied herein. Although for younger pastes, a similar trend was reported in [53] for carbonated pastes with the same water to cement ratios as in this study. The authors reported increasing reductions of porosity after carbonation for increasing water-to-cement ratios in the HCP.…”
Section: Degree Of Hydration and Total Porosity From Micro Ctsupporting
confidence: 88%
See 1 more Smart Citation
“…The results indicated that total porosity values for fully carbonated cement pastes were similar for the different water-to-cement ratios studied herein. Although for younger pastes, a similar trend was reported in [53] for carbonated pastes with the same water to cement ratios as in this study. The authors reported increasing reductions of porosity after carbonation for increasing water-to-cement ratios in the HCP.…”
Section: Degree Of Hydration and Total Porosity From Micro Ctsupporting
confidence: 88%
“…The micro-CT measurements revealed that the total porosity of ordinary HCP micro-beams was remarkably reduced after the accelerated carbonation treatment. The measured changes were in agreement with previous similar studies [53,54]. As the degree of hydration remained almost unchanged, the porosity reduction is attributed to the sole carbonation mechanism.…”
supporting
confidence: 92%
“…Therefore, increase in the number of curing days results in improved hydration and better compactment of the composite. Curing ensures the presence of free water content during hydration; this aids complete hydration of the cement [ 48 ]. The result presented highlights that 0.5 wt.…”
Section: Resultsmentioning
confidence: 99%
“…Carbonated cement paste in concrete is characterised by reduced compactness and/or evident absence of portlandite. In this pastes in the place of portlandite various calcium carbonates are formed [ 28 , 66 , 72 , 73 , 74 , 75 ]. As a result of carbonation on the surface of the portlandite, amorphous calcium carbonates are formed, which over time turn into vaterite, from which aragonite can be formed.…”
Section: Methodsmentioning
confidence: 99%
“…Infrared spectroscopy studies can be combined with other types of research, thus obtaining more accurate information about the composition of the carbonated paste. They can be complemented with XRD analysis [ 72 , 73 ], but can also be combined with thermal analysis [ 76 ]. Thermal analysis by the thermogravimetric (TG) method is a popular method that allows one to quantify the cement paste carbonation degree.…”
Section: Methodsmentioning
confidence: 99%